Вибір стратегії інформаційного впливу на інформаційне середовище віртуальної спільноти - Пелещишин, Андрій; Гумінський, Руслан (Видавництво Львівської політехніки, 2014)
Results of the research on the selection of informational psychological influence strategy on the internal information environment of virtual communities, created with the tools of social networks have been presented.
Keywords: показник інформаційної загрози; стратегія впливу; віртуальні спільноти